Data-driven environmental sustainability of supply chain for medical equipment - Atescan Yuksek, Yagmur; Afy-Shararah, Mohamed; Salonitis, Konstantinos (Elsevier, 2024)
Sustainable supply chain of medical equipment is challenging due to the inherent importance of having health-related components in-stock whilst balancing the economic and environmental impact of that. In general, to minimize the environmental impact of inventory management, physical inventory space and transportation amount can be lowered. However, in medical equipment, shortage of medical materials, and supplies could cause delays in providing adequate healthcare services. Therefore, effective inventory management is required to maintain a steady supply while minimizing the environmental and economic impact of supply chain. This study is aimed at assessing the environmental and economic impact of inventory for a medical equipment manufacturer. Inventory classification of the medical equipment manufacturer is performed using ABC analysis. After inventory classification using ABC, safety stock analysis is performed. Obtained inventory results are analysed both in terms of environmental sustainability using Life Cycle Assessment (LCA) approach and in terms of economic impact calculating cost of holding safety stock. An LCA model is created based on transportation of procurements. Impact assessment is performed to define most environmentally and economically impactful suppliers of the medical equipment manufacturer.
Presented at: 56th CIRP International Conference on Manufacturing Systems 2023, 24-26 October 2023, Cape Town, South Africa
Keywords: Environmental sustainability; supply chain; inventory management; medical equipment; Life Cycle Assessment